2010
DOI: 10.1007/s11136-010-9758-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting perceived quality of life of older persons with self-reported visual disability

Abstract: Significant differences were found between the groups on PQoL and seven of the other variables assessed. Of those, three were found to make a significant and unique contribution to the prediction of PQoL. These were satisfaction with life, ability to get around, and number of diagnosed health conditions reported in that order. Together, they accounted for 64% of the observed variance in PQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…On the basis of studies reported in the literature [21,34] one might expect a larger impact of physical and functional abilities in everyday tasks, insofar these individuals have a significant visual impairment which puts them at greater risk of problems in daily functioning. However, as these adults were not in an acute state, they may have already adapted to their living conditions and, as a result of resilience, flexibility and coping skills they may have the impact of the disabling condition they are experiencing on their own QoL [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of studies reported in the literature [21,34] one might expect a larger impact of physical and functional abilities in everyday tasks, insofar these individuals have a significant visual impairment which puts them at greater risk of problems in daily functioning. However, as these adults were not in an acute state, they may have already adapted to their living conditions and, as a result of resilience, flexibility and coping skills they may have the impact of the disabling condition they are experiencing on their own QoL [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…As far as several factors seem to play a role in QoL experienced by visually impaired individuals, LaGrow et al [34] in a longitudinal study of old persons analyzed the extent to which 11 different variables (e.g. age, sex, ability to see newsprint, satisfaction with ability to perform activities of daily living, ability to get around, feelings of social isolation or loneliness, and life satisfaction) affected perceived QoL.…”
Section: Introductionmentioning
confidence: 99%
“…This study constitutes a secondary analysis of the data reported in La Grow et al (2011). These data stem from the second data collection wave of Massey University's Health, Work and Retirement (HWR) study that was carried out in accordance with the treaty of Helsinki and approved by the Massey University Human Ethics Committee (MUHEC 05/90).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies showed that during the developmental stage of children and adolescents with visual impairment, they continue becoming more vulnerable to life circumstances [9]. Low vision is associated with negative consequences such as limitations in day-to-day activities [10,11], poor physical function [10], depressive symptoms [12][13][14][15][16], and low quality of life [17]. There is an internal relationship between sensory impairment, mental and social functioning, and communication [18].…”
Section: Introductionmentioning
confidence: 99%